2015
DOI: 10.1371/journal.pone.0123092
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Functional Characterization of Three Different Postzygotic Mutations in PIK3CA-Related Overgrowth Spectrum (PROS) Patients: Effects on PI3K/AKT/mTOR Signaling and Sensitivity to PIK3 Inhibitors

Abstract: Background PIK3CA-related overgrowth spectrum (PROS) include a group of disorders that affect only the terminal portion of a limb, such as type I macrodactyly, and conditions like fibroadipose overgrowth (FAO), megalencephaly-capillary malformation (MCAP) syndrome, congenital lipomatous asymmetric overgrowth of the trunk, lymphatic, capillary, venous, and combined-type vascular malformations, epidermal nevi, skeletal and spinal anomalies (CLOVES) syndrome and Hemihyperplasia Multiple Lipomatosis (HHML). Hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 18 publications
(24 reference statements)
2
69
0
Order By: Relevance
“…Patients with PIK3CA -dependent vascular anomalies and other tissue overgrowths may achieve even greater benefit from treatment with a selective p110α inhibitor, which would block mTORC1-independent functions of p110α not covered by rapamycin. As expected, PI3K inhibitors strongly suppress the proliferation of CLOVES syndrome cells in culture (Loconte et al, 2015). We expect that p110α inhibitors will be tested in CLOVES syndrome patients in the near future, and, toxicity issues notwithstanding, it is hoped that these drugs will offer the possibility of complete remissions not achievable with rapalog therapy.…”
Section: Tissue Overgrowth and Hamartoma Syndromessupporting
confidence: 75%
“…Patients with PIK3CA -dependent vascular anomalies and other tissue overgrowths may achieve even greater benefit from treatment with a selective p110α inhibitor, which would block mTORC1-independent functions of p110α not covered by rapamycin. As expected, PI3K inhibitors strongly suppress the proliferation of CLOVES syndrome cells in culture (Loconte et al, 2015). We expect that p110α inhibitors will be tested in CLOVES syndrome patients in the near future, and, toxicity issues notwithstanding, it is hoped that these drugs will offer the possibility of complete remissions not achievable with rapalog therapy.…”
Section: Tissue Overgrowth and Hamartoma Syndromessupporting
confidence: 75%
“…In order to characterize the mutation spectrum of patients with congenital/early childhood onset PROS without overgrowth of the brain, we performed an extensive literature search, and have presented the results together with the data of the seven patients described here [Kurek et al, ; Lindhurst et al, ; Rios et al, ; Castiglioni et al, ; Cohen et al, ; Emrick et al, ; Keppler‐Noreuil et al, ; Maclellan et al, ; Rasmussen et al, ; Couto et al, ; Limaye et al, ; Loconte et al, ; Luks et al, ; Osborn et al, ; Castillo et al, ; Hucthagowder et al, ; Mirzaa et al, ; Tripolszki et al, ]. We found that the three highly recurrent cancer‐associated mutations, p.(Glu542Lys), p.(Glu545Lys), and p.(His1047Arg) [Mirzaa et al, ], can be seen in about 70% of patients with PROS; whereas p.(Cys420Arg) and p.(His1047Leu) accounts for nearly 20% of the patients (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of these activities, rapamycin has antiproliferative effects and could prevent tissue overgrowth in patients with PIK3CA mutations . Furthermore, specific inhibitors for other components of the PI3K‐AKT‐mTOR and other interconnected signalling pathways have been developed . Consequently, precise knowledge of the mutated gene and specific mutations is a prerequisite for ascertainment of treatment options in the future as part of personalized healthcare delivery.…”
Section: Discussionmentioning
confidence: 99%